Firm-level entry and exit over the Danish business cycle - Svend Greniman Andersen; Filip Rozsypal (Danmarks Nationalbank, 2018)
We use a new registry micro level data set to study firm dynamics in Denmark. A unique feature of the data allows us to gain more information about older firms (operating for 30+ years), and an important proportion of these firms shows deteriorating productivity and rising exit rates. We find supportive evidence for other US-based stylized facts, such as young firms being more likely to exit and to grow faster over time. However, it seems to take longer for Danish firms to reach maturity. The Danish data also do not show any signs of a slowdown in the entry rate. Finally, we do not find long-run scarring effects on firms entering in recessions. However, fluctuations in the entry rate have persistent effects on the long-run aggregate volume of value added.
Keywords: D22; E23; E24; E32; 330; Firm dynamics; firm-level microdata; business cycles